EXPLORING EMPLOYEE SATISFACTION IN AICE GROUP INDONESIA - Xujie, Xujie; Tan, Jacob Donald (FEB Universitas Sam Ratulangi Manado, 2021)
Abstract: AICE Group is a licensed company from Singapore and has 20 years of experience in the ice cream industry. Fundamentally, employees are the most important asset to develop the competitive advantage of a company. Thus, AICE Group needs to retain and motivate its current employees. In this qualitative study, the researchers inquired into the issues and strategies of employee satisfaction in the company by employing a single instrumental case study and applying interviews, observations, and field notes. There are 8 employees from 5 departments who were approached for this study. The findings evinced a mini-model theory that guides AICE in Indonesia to enhance employee satisfaction for the longevity of the firm. The mini-model theory consists of Communicative Leadership, Language Barrier, Supervision, AICE Group Culture, Co-Workersâ€™ Relationships, Rational Salaries, Rational Benefit, Job Descriptions, Standard Operating Procedure (SOP), Problem-Solving Orientation, Cultural Diversity, Government Regulation Compliance, and Employee Feedback. Finally, the researcher also suggests quantitative research for further research.Â Abstrak: AICE Group adalah perusahaan berlisensi dari Singapura dan memiliki pengalaman 20 tahun di industri es krim. Pada dasarnya, karyawan merupakan aset terpenting untuk mengembangkan keunggulan kompetitif suatu perusahaan. Oleh karena itu, AICE Group perlu mempertahankan dan memotivasi karyawannya saat ini. Dalam studi kualitatif ini, para peneliti menyelidiki masalah dan strategi kepuasan karyawan di perusahaan dengan menggunakan studi kasus instrumental tunggal dan menerapkan wawancara, observasi, dan catatan lapangan. Ada 8 karyawan dari 5 departemen yang didekati untuk penelitian ini. Temuan ini membuktikan teori model mini yang memandu AICE di Indonesia untuk meningkatkan kepuasan karyawan demi kelangsungan perusahaan. Teori model mini terdiri dari Communicative Leadership, Language Barrier, Supervision, AICE Group Culture, Co-Workersâ€™ Relationships, Rational Salaries, Rational Benefits, Job Descriptions, Standard Operating Procedure, Problem-Solving Orientation, Cultural Diversity, Government Regulations Compliance, and Employee Feedback. Terakhir, peneliti juga menyarankan penelitian kuantitatif untuk penelitian selanjutnya.